Overcoming disability barriers: The journey to social acceptance and self-fulfillment in R. J. Palacio’s wonder - Hashim, Abdel Mohsen Ibrahim; Hassan, Ashraf Abdeltawab; Alshemi, Radwa Atef; Alzahrani, Fahd Ali; Zamakhshari, Nahla; Jarah, Nora Yahya (Edelweiss Applied Science and Technology, 2024)
The main aim of this article is to provide a reading of R. J. Palacio’s Wonder, tracing the journey of August Pullman, the protagonist of the novel, as he moves from exclusion and frustration to social acceptance and self-fulfillment. Despite being born with a severe facial deformity, the ten-year-old boy August, or "Auggie" as he is often called, demonstrates remarkable resilience in his efforts to integrate into his social environment. Though initially disappointed by the narrow-mindedness of those around him, who have treated him offensively because of his physical abnormality, Auggie insists on overcoming the barriers of disability till he succeeds in showing his talents as a distinguished person. While some of his school peers have received him with rejection and rudeness, he goes on, finding solace in the support of those who have embraced him with love, kindness, and care, helping him find his way in society. The researchers employ both the narrative approach and the analytical approach to recount and examine the unique life experiences of Auggie as presented in the novel. After a series of ups and downs, Auggie successfully fits into his community, fulfilling the goals he has long yearned for and gaining the respect and admiration of his family, teachers, and friends.